Primary breast lymphoma: a case report - Taheri, Hafsa; Hmila, Asma; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Primary breast lymphoma is a primary degeneration of the breast lymphoid tissue. Study aim to describe primary breast lymphoma; its clinical presentations, histological particularities and management methods. A 33 years-old patient with no medical history underwent a breast surgery. Its anatomo-pathological study, supplemented by immunohistochemistry, showed a primary breast lymphoma. The extension assessment was negative. The patient underwent chemotherapy with regression of the tumor. Breast lymphomas are rare conditions. Its clinical symptomatology is polymorphic and the imaging aspects are non-specific. It should be evoked in front of any breast tumor in order to avoid heavy breast surgery since the basic treatment is based on chemotherapy.